Frequency of BK virus nephropathy in graft dysfunction biopsies - TUĞLULAR, ZÜBEYDE SERHAN (JOHN WILEY & SONS INC, 2007)
Background. BK virus nephropathy is the most common type of viral disease to occur following renal transplantation. Although its frequency differs according to transplantation center, the rate is between 1.5% and 20%. Diagnosis can be established histologically by renal allograft biopsy. The aim of this study was to determine the frequency of BK virus nephropathy in patients who had had a renal biopsy for graft dysfunction at our center. Methods. Biopsies received in the last 3 years from patients with graft dysfunction were used in the study. We have found the BK virus in biopsies of 5 of 41 patients (11%). All these patients had been treated with immunosuppressive drugs following transplantation surgery. Biopsies were performed because of disturbance of renal function. Only 1 patient had had a urinary examination. Morphological diagnosis of BK virus nephropathy was followed by serological examination. Results. The most frequent morphological changes with BK virus infection in our samples were basophilia, nuclear inclusions, and nuclear enlargement on tubular epithelium. Decoy cells were not found in the biopsy from the only patient who had had a urinary examination. Treatment of the patients with BK virus nephropathy with immunosuppressive drugs has been reduced, and antiviral treatment has been started. Conclusion. BK virus nephropathy should be kept in mind in the differential diagnosis of transplant rejection and drug toxicity.
Keywords: RENAL-TRANSPLANT RECIPIENTS; HUMAN POLYOMA-VIRUS; INTERSTITIAL NEPHRITIS; INFECTION; DIAGNOSIS; DISEASE